2020
DOI: 10.18632/aging.202157
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of prognostic nomograms for early-onset locally advanced colon cancer

Abstract: Background: The incidence of colorectal cancer in patients younger than 50 years has been increasing in recent years. Objective: Develop and validate prognostic nomograms predicting overall survival (OS) and cancer-specific survival (CSS) for early-onset locally advanced colon cancer (EOLACC) based on the Surveillance, Epidemiology, and End Results (SEER) database. Results: The entire cohort comprised 13,755 patients with EOLACC. The nomogram predicting OS for EOLACC displayed that T stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 26 publications
3
21
0
Order By: Relevance
“…Our study shows more strength than previous related nomograms. On the one hand, unlike previous nomograms that just included patients with colon cancer [38][39][40], our nomogram focused on patients with colon cancer and those with rectal cancer, no matter the stage situation. On the other hand, our nomogram involved some distinct variables, such as SES and LNR, which were also reported to be important predictors of prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our study shows more strength than previous related nomograms. On the one hand, unlike previous nomograms that just included patients with colon cancer [38][39][40], our nomogram focused on patients with colon cancer and those with rectal cancer, no matter the stage situation. On the other hand, our nomogram involved some distinct variables, such as SES and LNR, which were also reported to be important predictors of prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Noriyuki,H, et al reported LMR was associated with cancer-speci c survival (CSS) of esophageal cancer patients after curative esophagectomy. In particular, a low LMR was an independent predictor of poor survival in non-elderly patients [16].…”
Section: Discussionmentioning
confidence: 92%
“…The risk score does not always increase with age in our nomogram. Previous research indicated that young cancer patients suffered a higher risk of lymph node metastasis [27][28][29], which may be the reason why the risk score of PDAC patients under 50 is higher than that of ones aged 51-60. Limitations of this study include: (1) the use of retrospective data; (2) detailed treatment information for included patients were not recorded in the SEER cohort, and we cannot investigate specific options, including R0 or not, preoperative or postoperative chemotherapy in the survival of PDAC patients; (3) other important factors, such as proximity/involvement of major vascular structures, CA 19-9, and patient comorbidities should also be minded.…”
Section: Discussionmentioning
confidence: 98%